ANIMAL AS A SUBJECT. ON META-STRATEGIES OF COLONIZING THE NATURE - Mamzer, Hanna (Porównania, 2014)
Postindustrial societies undertake forms of colonization, which derive from specificity of agriculturally-based societies. Industrial revolution had equipped human kind in tools that are being applied in order to conquest the natural world. In contemporary humanistic discourse one can observe stronger and stronger stream of discussing issues related to human domination and exploitation of the nature. All of protets against those procedures aim at empowering natural surroundings of human kind in order to limit colonization process. While looking at colonization in socio-cultural aspects and environmental aspects, one may notice many similarities. Is it possible to name meta-strategies used in colonization processes?